- English

×

Enter the function and choose the variable. Hit the **Calculate** button to find the second derivative usind second derivative calculator.

The second derivative calculator is an online tool that performs differentiation twice on a function. It can find both first and second derivatives.

Moreover, the 2nd derivative calculator gives the complete solving process with step by step solution.

The second derivative test calculator is an easy-to-use tool. Follow these steps to find second derivative.

- Enter the function.
- Choose the variable.
- Confirm the displayed function from the display box.
- Click calculate.

To understand the differentiation procedure, click on the ‘+’ icon in results. It will give a step-wise guide. You can also download the ‘PDf’ copy of the detailed result.

The derivative taken of the same function for the second time is known as the second derivative. It is the same as the first derivative except for the notation.

The second derivative is represented by two dots over the variable or two dashes on f in the notation f(x) e.g f’’(x).

A graphical representation of 2nd derivatives can be seen below.

There is no separate process or formula for the second derivative. It is the same as the first. The second derivative is differentiation performed on the derivative of a function.

Let’s see an example of the second derivative.

**Example 1:**

Calculate the second derivative for function **x =** **Sinx + x**^{2}

**Solution:**

**Step 1:** Arrange the function.

f(x) = x^{2} + sinx

**Step 2:** Find the first derivative.

f’(x) = d/dx [x^{2} + sinx]

f’(x) = d/dx [x^{2}] + d/dx[sinx]

f’(x) = 2x + cosx

**Step 3:** Find the 2nd derivative.

f’’(x) = d/dx [2x + cosx]

f’’(x) = d/dx [2x] + d/dx[cosx]

f’’(x) = 2 - sinx

**Example 2:**

Find the second derivative for **a*(x**^{2}**+b)**.

**Solution:**

**First derivative.**

**Step 1:** Apply derivative.

f’(x)= d/dx [a*(x^{2}+b)]

**Step 2:** Take constant out.

f’(x)= a d/dx (x^{2} + b)

**Step 3:** Apply constant rule and power rule.

f’(x)= a (2*x^{2-1} + 0)

f’(x)= a (2x + 0)

f’(x)= 2ax

**Second Derivative:**

**Step 4:** Apply the second derivative.

f’’(x) = d/dx (2ax)

**Step 5:** Take the constant out.

f’’(x) = 2a d/dx (x)

f’’(x) = 2a (x^{1-1})

**f’’(x) = 2a**

**Example 3:**

What is the second derivative of **sinx + x/2**?

**Solution:**

**First derivative:**

**Step 1:** Apply the derivative.

f’(x) = d/dx (sinx + x/2)

**Step 2:** Apply the Sum rule.

f’(x) = d/dx(sinx) + d/dx(x/2)

**Step 3:** Take out the constant.

f’(x) = cosx + (½)d/dx(x)

f’(x) = cosx + ½

**Second derivative:**

**Step 4:** Apply the second derivative.

f’’(x) = d/dx (cosx + ½ )

**Step 5: **Apply the sum rule.

f’’(x) = d/dx (cosx) + d/dx(½)

**Step 6: **Constant rule.

f’’(x) = -sinx + 0

X